Pemanfaatan Geogebra sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar Keterampilan Matematika - Madhona Widyaningrum (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of learning mathematics is in line with the demands of the Industrial Revolution 4.0, humans are required to have a number of skills to acquire, select, sort and manage information.  The most obvious impact for students and educators is to be able to take advantage of this digitalization era in learning, especially in the current pandemic era.  One of them is the use of software in mathematics learning is GeoGebra.  GeoGebra is dynamic geometry software.  The software can be used as a medium that can help the teaching and learning process of mathematics in the classroom.  The study in this paper aims to describe the use of GeoGebra Software as an effective and efficient learning media innovation that can be used in learning mathematics skills. Thus improving the learning outcomes of math skills.